A new species of Eumeces Wiegmann 1834 (Sauria: Scincidae) from Iran - Faizi, Hiva; Rastegar-Pouyani, Nasrullah; Rastegar-Pouyani, Eskandar; Nazarov, Roman; Heidari, Nastaran; Zangi, Bahman; Orlova, Valentina; Poyarkov, Nikolai (Zootaxa, 2017)
We describe a new species of skink in the genus Eumeces Wiegmann 1834 from Iran. Eumeces persicus sp. nov. is a medium-sized skink, distinguished by two clear, wide, and brown lateral lines extending from the ear opening to the hindlimbs, with scattered light orange spots, and two median rows of dorsal scales broadly enlarged in eight longitudinal rows. The new species ranges from southern Tehran to Kerman Province along the eastern slopes of the Zagros Mountains towards the Iranian plateau. We provide morphological comparisons of the new species with other Eumeces species from the region and molecular analyses of two mitochondrial markers (16S and Cytb). We also present taxonomic and phylogenetic accounts, with an updated identification key for the genus Eumeces in Iran and surrounding regions.